Adipose-derived stem cells undergo differentiation after co-culture with porcine limbal epithelial stem cells - Sikora, Bartosz; Skubis-Sikora, Aleksandra; Kimsa-Furdzik, Małgorzata; Ciszek, Wojciech; Kostrzewski, Marek; Stojko, Jerzy; Mazurek, Urszula; Gola, Joanna (Stem cell research, 2019)
Mesenchymal stem cells (MSCs) are objects of interest in regenerative medicine. They are used for various therapies such as for the regeneration of bone, chondrocytes and other tissues. Adipose derived stem cells (ADSCs) inter alia are particularly easy to access, they are relatively abundant in fat tissue. ADSCs could be differentiated into many types of cells. To date, it has been proven that ADSCs only differentiate into mesodermal cell lineages. In this study, we present the differentiation of ADSCs into the corneal epithelium. Human ADSCs were placed in a co-culture with porcine limbal epithelial stem cells (LESCs). After 14 days of cultivation, total RNA was extracted for the analysis of the molecular markers (expression of genes of interest). The gene expression was assessed by real-time RT-qPCR. The expression of the surface molecular markers of ADSCs is modulated after co-culturing. We have observed the decrease in CD73, CD90 and CD105 mRNA expression, while the expression of mRNA coding for CK3 and CK12 mRNA was increased in ADSCs co-cultured with porcine limbal epithelial stem cells as compared to the control. We conclude that the co-culture of LESCs and ADSCs changed ADSCs’ molecular markers gene expression indicating initiation of differentiation towards limbal cells.